2015
DOI: 10.4172/2167-7948.1000193
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging of Nodal Metastases in the Central Compartment in Thyroid Cancer: is it Possible to Increase Sensitivity

Abstract: Background and Purpose: Ultrasound imaging criteria for cervical lymph nodes were set mainly to increase sensitivity. However, unlike the lateral neck compartment, the challenge in the central compartment is the low sensitivity of Ultrasonography. We performed this study to evaluate whether the sensitivity of Ultrasonography could be increased by considering any detected lymph node in the central compartment as malignant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…However, there is controversy regarding the value of preoperative US for the diagnosis of LNM. Some studies have obtained optimistic results, showing that the sensitivity and specificity of preoperative US in detecting central LNM were 62-95% and 75-90%, respectively (16,17). However, more studies have shown that the sensitivity of US in detecting central LNM was unsatisfactory (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is controversy regarding the value of preoperative US for the diagnosis of LNM. Some studies have obtained optimistic results, showing that the sensitivity and specificity of preoperative US in detecting central LNM were 62-95% and 75-90%, respectively (16,17). However, more studies have shown that the sensitivity of US in detecting central LNM was unsatisfactory (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…However, lateral neck dissection is only done therapeutically in cases where there is confirmed nodal metastasis in the lateral compartment. Meanwhile, central compartment lymph node dissection (LND) is routinely performed in many institutions as a prophylactic measure to improve staging accuracy, reduce nodal recurrence risk, reduce thyroglobulin level postoperatively, and consequently avoid re-operation in the central neck 13 . Prophylactic neck dissection is limited only to the central compartment, and, on the other hand, therapeutic neck dissection is only performed when there is proof of metastatic lateral LNs involvement either radiologically or histopathologically 14 .…”
Section: Introductionmentioning
confidence: 99%